ASSESSMENT OF COMPUTERIZED AND MANUAL ANALYSIS OF SLIDES PROCESSED IN SINGLE CELL GEL ELECTROPHORESIS ASSAY - Dikilitas, Murat; KOÇYİĞİT, ABDÜRRAHİM; KOÇYİĞİT, ABDÜRRAHİM (My University, 2012)
The comet assay, also called the single-cell gel electrophoresis (SCGE) assay, is a rapid, simple and sensitive microgel electrophoresis technique for measuring DNA damages (strand breaks and alkali-labile sites) in individual cells. The technique enables us to evaluate the mechanisms of genotoxic and cytotoxic effects of physical and chemical agents on living organisms. In principal, isolated DNA from cells are embedded in agarose, was unwound in an alkaline buffer, and is subjected to a weak electric current in which the broken negatively charged DNA becomes free to move towards the anode. The migrated DNA structures stained with a fluorescent dye resemble a shape of a -comet- when observed by fluorescence microscopy. The intensity of the comet tail relative to the head reflects the number of DNA breaks. The analysis of comets is generally carried out with either the use of a computer image-analysis program or with manual scoring through a scale. There are several image analysis programs commercially available providing a large number of measurement outcomes (i.e., tail length, tail moment, etc.) to evaluate the extent of DNA damage. However, these are highly expensive methods and need to be updated on a regular basis. In this study, we compared analysis of the same slides by CASP (R) (comet analysis software program) and a manual method. The manual method for comet analysis provided good and reliable data and correlated well with the parameters, such as TM (tail moment), OTM (Olive tail moment), comet length etc., obtained from the CASP (R). However, the analysis of comets with CASP (R) minimized time, faults and expertise but offered a large number of comets to be analyzed with many valuable parameters. The image analysis program is freely available and meets the necessity of parameters of many commercially available programs.